The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/nph.18082
|View full text |Cite
|
Sign up to set email alerts
|

Plant migration under long‐lasting hyperaridity – phylogenomics unravels recent biogeographic history in one of the oldest deserts on Earth

Abstract: The post-Miocene climatic histories of arid environments have been identified as key drivers of dispersal and diversification. Here, we investigate how climatic history correlates with the historical biogeography of the Atacama Desert genus Cristaria (Malvaceae).We analyze phylogenetic relationships and historical biogeography by using nextgeneration sequencing (NGS), molecular clock dating, Dispersal Extinction Cladogenesis and Bayesian sampling approaches. We employ a novel way to identify biogeographically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 81 publications
(143 reference statements)
3
9
0
Order By: Relevance
“…More recently, a study of Schwarzer et al (2010) indicated that elements of typical loma vegetation and even presumed loma endemics may be found in certain habitats along the southern Peruvian precordillera reaching elevations of up to 2,600 m asl. Ruhm et al (2020) demonstrated a relative floristic coherence along the precordillera from Chile to southern Peru, confirming the presence of a "floristic corridor" along the Andean precordillera of Peru and Chile as previously suggested (Moreno et al, 1994) and shown by phylogenetic studies (e.g., Luebert et al, 2009;Luebert and Weigend, 2014;Böhnert et al, 2022). This is in stark contrast to the "floristic break" between the loma floras of Peru and Chile, respectively, as previously hypothesized in floristic (Rundel et al, 1991;Galán de Mera et al, 1997;Pinto and Luebert, 2009;Manrique et al, 2014) and phylogenetic studies (Gengler-Nowak, 2002;Merklinger et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…More recently, a study of Schwarzer et al (2010) indicated that elements of typical loma vegetation and even presumed loma endemics may be found in certain habitats along the southern Peruvian precordillera reaching elevations of up to 2,600 m asl. Ruhm et al (2020) demonstrated a relative floristic coherence along the precordillera from Chile to southern Peru, confirming the presence of a "floristic corridor" along the Andean precordillera of Peru and Chile as previously suggested (Moreno et al, 1994) and shown by phylogenetic studies (e.g., Luebert et al, 2009;Luebert and Weigend, 2014;Böhnert et al, 2022). This is in stark contrast to the "floristic break" between the loma floras of Peru and Chile, respectively, as previously hypothesized in floristic (Rundel et al, 1991;Galán de Mera et al, 1997;Pinto and Luebert, 2009;Manrique et al, 2014) and phylogenetic studies (Gengler-Nowak, 2002;Merklinger et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…We would find this hypothesis supported, if habitat suitability models indicated a pronounced gap for loma vegetation (Rundel et al, 1991;Pinto and Luebert, 2009). Conversely, we propose that (3) the precordillera floras of Peru and Chile show a closer connectivity (Luebert et al, 2009;Böhnert et al, 2022). We here expect a gradual latitudinal floristic change-over in a continuous belt of suitable habitat.…”
Section: Introductionmentioning
confidence: 66%
“…(2019). The restriction site‐associated DNA sequencing method provided a much higher degree of phylogenetic resolution, which is in line with an increasing number of systematic as well as taxonomic studies in recent years (e.g., Andrews & al., 2016; Merklinger & al., 2021; Yahara & al., 2021; Böhnert & al., 2022). This is the first study using a RADseq approach within Asparagaceae in a genus‐wide phylogenetic context and proves to be able to untangle the complex evolutionary processes of Mediterranean geophytes, which might be responsible for the cryptic taxonomic history of this group (Garbari & Greuter, 1970; Speta, 1982; Davis & Stuart, 1984; Grundmann & al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach shows that quantitative evaluation of nonsequenced specimens that were identified based on morphological characters and using existing prephylogenetic treatments can be successful in evaluating the status of so‐called nested singletons that were found in phylogenetic analyses. Such singletons are frequent in published molecular phylogenetic trees based on multiple sequence alignments of few to multiple loci (Bengtson et al, 2021 ; Lu‐Irving et al, 2021 ; García‐Moro et al, 2022 ) and as well in phylogenomic analyses using RAD (Böhnert et al, 2022 ) or hyb seq data (Jones et al, 2019 ; Xu & Chen, 2021 ). Under normal circumstances, one would target several specimens of a species complex to address species delimitation, then also ideally combining molecular, morphological, ecological, and distributional data in an integrative taxonomy approach.…”
Section: Discussionmentioning
confidence: 99%